Pendekatan Hukum Perlindungan Anak di Bawah Umur dalam Penyalahgunaan Narkoba - Evi Apriani (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Drug abuse among children is a serious issue requiring special attention in prevention and handling efforts. This study employs a normative juridical approach to identify challenges and propose solutions regarding legal protection for children involved in drug abuse in Indonesia. The results indicate that existing regulations still face various obstacles in protecting children, particularly in applying restorative justice principles and rehabilitation tailored to children's conditions as offenders. Effective legal protection must consider the psychological and social aspects of the child while emphasizing strong collaboration between the government, non-governmental organizations, and the community to support prevention and rehabilitation efforts. A thorough understanding of the implementation of the Child Protection Law and the Narcotics Law is crucial to enhancing comprehensive legal protection for children in Indonesia. This approach aims to create a more humane system focused on the child's future, enabling them to break free from the cycle of drug abuse and have the opportunity to make positive contributions to society.